The Development of Web Diagnostic Test as a Misconception Tool in Work and Energy - Kurniawan, Wawan; Al Amin, M.; Sandra, Rizka Octavia; Iqbal, Muhammad (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2023)
At this time, the assessment and measurement of the concept’s level of understanding are considered less effective. This is due to the use of conventional media. With this in mind, researchers are interested in conducting research on developing assessments and measuring the understanding of concepts using web media. Web of the comprehension level test will be automatically stored in real-time on the system so that educators can process the data on the results of the misconception test and can also be seen by students as the results of the comprehension level test. This study aims to develop a web diagnostic test and identify students’ misconceptions about effort and energy as the subject matter. This study uses the ADDIE development model. The results obtained from this study were that the responses given by users showed good results. This means that the media used to measure student misconceptions is interactive enough to be used as a support in the learning process.